HUBUNGAN ANTARA SELF-EFFICACY DAN MOTIVASI BERPRESTASI SISWA KELAS XI IPA DALAM MATA PELAJARAN KIMIA DI SMA NEGERI 3 PONTIANAK - Bellya Firsty Novanda (Universitas Muhammadiyah Pontianak, 2018)
The students’ average score on Chemistry subject has still low. This has caused not only by the level of the difficulty but also the low of the students’ self-efficacy and motivation. This study aimed at finding out the students’ self-efficacy, motivation, and the correlation of self-efficacy and achievement motivation among the ninth grade Science class students of SMA Negeri 3 Pontianak. Using descriptive correlational design, as many as 66 students of the ninth grade Science class participated in this study. The self-efficacy measurement was conducted by using self-efficacy scale which was adopted from the Bandura scale with a reliability coefficient of 0.86, whereas, the achievement motivation measurement conducted by using achievement motivation scale based on The Mehrabian Achieving Tendency from Mehrabian 1993 with a consistency internal reliability of 0.92. The study reveals that 53,03% of students obtained medium self-efficacy, and 60,61% of students students had average achievement motivation. The Pearson Product Moment correlation test indicated that there was a positive and significant correlation between self-efficacy and achievement motivation by 0,278 which was considered into low category with sig value (2-tailed) of 0.024. Keywords: Chemistry, Correlation, Achievement Motivation, Self-efficacy